Urban Noise Annoyance Between 2001 and 2013 – Study in a Romanian City - Diana Ioana POPESCU; Iuliana Fabiola MOHOLEA; Radu Mircea MORARIU-GLIGOR (Archives of Acoustics, 2013)
The paper presents results of three socio-acoustic surveys conducted in an interval of twelve years, between 2001 and 2013, in a large Romanian city, Cluj-Napoca. The purpose of the surveys was to assess the awareness of residents on urban noise and the extent to which the noise environment affects their everyday life, behavior and health. The surveys were conducted in 2001, 2009 and 2013. The questionnaire used in the first survey had 16 questions and it was verified prior to study through a pilot survey, being corrected and improved. For the second and the third study, the questionnaire was enriched with eight more questions, regarding essentially the description of the residential area, criteria for its selection and also awareness about the noise map of the city. The analysis of responses defines the main characteristics of the local pattern of annoyance and reaction of the urban population to the environmental noise.